The Influence of Breastfeeding Support Group on the Attitudes And Behavior of Breastfeeding Mothers - Putri Widita Muharyani; Karolin Adhisty; Nurna Ningsih; Herliawati Herliawati; Dwi Roudhotul Jannah (GLOBAL HEALTH SCIENCE GROUP, 2025)
Breast milk is the best nutrition for babies aged 0-6 months. Breast milk is beneficial for the growth and development of children. Lack of knowledge of breastfeeding mothers and minimal support from the environment have resulted in the coverage of exclusive breastfeeding not reaching the target. The purpose of this study was to determine the effect of breastfeeding support groups on the attitudes and behavior of breastfeeding mothers .This study used a pre-experimental design of one group pretest and posttest. The sample was selected using non-probability sampling of the purposive sampling type. The number of samples was 34 breastfeeding mothers in the working area of the Sako Palembang Health Center. Data collection used a questionnaire that had been tested for validity with an r table value of 0,361 and Cronbach Alpha reliability> 0.60. Data analysis used the Mc Nemar test for attitudes and behavior. The results showed that there were differences in the attitudes and behavior of mothers before and after the intervention, p value 0.000 (p < 0.05). Breastfeeding support groups can be used as one solution in educating breastfeeding mothers.